Grafting of acrylonitrile onto cellulosic material derived from bamboo (Dendrocalamus strictus) (eXPRESS Polymer Letters)
Bamboo, a lignocellulosic biopolymer material, is of interest as feedstock for production of cellulose derivatives by chemical functionalization. Optimization of grafting of acrylonitrile onto cellulosic material (average Degree of Polymerization 816), isolated from bamboo (Dendrocalamus stictus) was performed by varying the process parameters such as duration of soaking of cellulosic material in ceric ammonium nitrate solution, ceric ammonium nitrate concentration, polymerization time, temperature of reaction and acrylonitrile concentration to study their influence on percent grafting and grafting efficiency. Graft copolymerization of acrylonitrile onto cellulosic material derived from bamboo (Dendrocalamus strictus) in heterogenous medium can be initiated effectively with ceric ammonium nitrate. The optimum reaction conditions obtained for grafting of acrylonitrile onto cellulosic material were: duration of dipping cellulosic material in ceric ammonium nitrate solution 1 hr, ceric ammonium nitrate concentration 0.02 M, acrylonitrile concentration 24.6 mol/anhydroglucose unit, temperature of reaction 40°C and polymerization time 4 hrs. The percent grafting for optimized samples is 210.3% and grafting efficiency is 97%. The characterization of the grafted products by means of FTIR and Scanning Electron Microscopy furnished the evidence of grafting of acrylonitrile onto the cellulosic material.